A randomized controlled feasibility trial of online compassion‐focused self‐help for psoriasis. (1st June 2022) - Muftin, Zina; Gilbert, Paul; Thompson, Andrew R.
Summary: Background: People with psoriasis can experience psychological distress that might be amenable to psychosocial self‐help. Objectives: This study tested the feasibility and acceptability of two theoretically developed self‐help interventions designed to reduce feelings of shame and improve quality of life. Methods: A randomized controlled feasibility trial was conducted comprising 130 participants with psoriasis who were randomly allocated to receive either compassion‐based self‐help (n = 65) or mindfulness‐based self‐help (n = 65), over a 4‐week period. Both interventions were provided online. Results: The interventions were found to be acceptable, with over 70% of study completers reporting that they found the materials helpful. Of the 130 participants, 92 completed the study, with attrition at 29%. Both interventions showed modest yet statistically significant reductions in shame (Cohen's d = 0.20) and improvements in quality of life (Cohen's d = 0.40). Conclusions: Self‐help based on compassion and mindfulness is acceptable to users, and can reduce feelings of shame and improve quality of life for people living with psoriasis. What is already known about this topic? Psoriasis can be associated with psychological distress. Various forms of psychological intervention have been tested; however, few compassion based interventions have been developed or trialled. What does this study add? This study demonstrates that compassion‐based self‐help is acceptable to people with psoriasis. This study provides provisional evidence of effectiveness of compassion based self‐help in reducing feelings of shame and improving quality of life for people living with psoriasis.